Converting Commercial Sewing Threads into High‐Performance and Flexible/Wearable Fiber‐Shaped Supercapacitors via Facile Vapor Deposition Polymerization. Issue 18 (14th May 2019) - Gao, Xue; Xiao, Xinyu; Dong, Bin; Hu, Jing; Tang, Sheng; Qi, Wen; Zou, Dechun
Abstract: Fiber‐shaped supercapacitors (FSSCs) are expected to motivate the development of wearable electronics. However, their high cost and complex operations limit their industrial production. Herein, commercial sewing threads are utilized as fiber substrates to prepare FSSCs via facile methods. The sewing threads become conductive after poly(3, 4‐ethylenedioxythiophene) (PEDOT) uniformly grew on the porous surface by in situ polymerization of vacuum‐deposited 2, 5‐dibromo‐3, 4‐ethylenedioxythiophene. Then, MnO2 nanoflakes electrochemically grow on the conductive threads and the PEDOT layer uniformly wraps the flake surface, thereby improving the electrochemical performance. The FSSCs based on PEDOT/MnO2 /PEDOT sandwich structure exhibit a high specific capacitance of 53.89 mF cm –1 (132.02 mF cm –2 ), an energy density of 3.07 μWh cm –1 (7.51 μWh cm –2 ), and a power density of 21.3 μW cm −1 (52.3 μW cm –2 ). Mild polymerization plays a vital role in converting the sewing threads into fiber electrodes with excellent properties. It confers electrodes with a robust adhesion ability, which results in excellent stability. The intrinsic knittability of sewing threads endows the FSSCs with outstanding flexibility. The low cost of the materials and facile preparation methods promote the large‐scale production and wide application of FSSCs. Moreover, these FSSCs based on sewing threads provide insight into the opportunity to develop smart and wearable electronics. Abstract : The facile vapor deposition polymerization could prepare uniform conductive film on porous substrate. A flexible FSSC with excellent performance was prepared via facile polymerization and electrodeposition. And this is the first report to prepare high‐performance FSSC based on commercial sewing threads without the utilization of metal or carbon materials.